Research on the impact of social exclusion on conspicuous consumption: The moderating role of mindfulness - Jiang, Zhi-Wei; Chang, Shu-Ya (Edelweiss Applied Science and Technology, 2025)
This study examines the relationship between social exclusion and conspicuous consumption behavior, with a focus on the mediating role of psychological distress. This study employed a questionnaire survey, gathering data from 561 participants (working-age population in mainland China) using purposive sampling. Statistical techniques, including structural equation modeling, Pearson correlation analysis, and multiple regression analysis, were applied to test the proposed theoretical model. The findings reveal that social exclusion significantly promotes conspicuous consumption, with psychological distress acting as a mediator. Additionally, mindfulness moderates the effect of social exclusion on conspicuous consumption, although it does not influence the relationship between social exclusion and psychological distress. The study’s theoretical contribution lies in identifying the mechanism by which social exclusion impacts conspicuous consumption, providing a deeper understanding of the psychological processes behind such behaviors. The practical implications suggest that mindfulness-based interventions could be effective in reducing conspicuous consumption among individuals experiencing social exclusion, offering a potential strategy for managing consumption patterns in a social context.